Motives for small Finnish textile companies to base their business on environmental sustainability : Researching possible disruptive traits - Teikari, Hanna (My University, 2022)
This research focuses on finding out the motives behind running a business that is based on environmental sustainability from a Finnish micro textile company perspective. An additional perspective of this research is to find out whether there is disruptive potential among these types of companies. The awareness of environmental issues has increased remarkably recently and this reflects to the operations of different sized companies. Large established fast fashion companies have not originally been based on environmental sustainability but some of them have already taken actions towards it while still having a large customer base. This research aims at finding out how a small environmental sustainability based companies can compete with the large companies holding on to their principles in one of the most competed industries. The other perspective to this research is to bring up the concept of disruption, clarifying its meaning, and find out whether Finnish micro-sized companies are disruptive or have disruptive potential. This perspective will be approached by investigating the concept created by Christensen but also by taking into consideration the changed meaning in colloquial language. This study demonstrates researching a small sample that the motives of these types of companies lean strongly towards social and community motives while having characteristics of the entrepreneurs’ personal non-financial motives. This indicates that there is a genuine concern towards the environmental state, and readiness to fight the negative effects of fashion industry. Taking the strictly formed concept of disruptiveness and the changed meaning in colloquial language into consideration, it is challenging to say whether these types of small companies are truly disruptive or not, but there can be perceived some disruptive potential. This research addresses the need for further complementary research and it can be stated that diagnosing disruptiveness may not be univocal before a disruption itself has taken place.

Tämä tutkimus keskittyy selvittämään motiiveja ympäristökestävän yritystoiminnan taustalla. Tutkimuskohteena ovat suomalaiset mikrokokoiset tekstiilialan yritykset. Tutkimuksessa tutkitaan motiivien ohella mahdollista disruptiopotentiaalia. Tietoisuus ympäristöongelmista on ollut viimeaikoina huomattavassa kasvussa ja tämä heijastuu myös eri kokoisten yritysten toimintoihin. Suuret pikamuotifirmat eivät ole alun perin perustaneet yritystoimintaansa ympäristövastuullisuuteen, mutta ovat ottaneet askelia sitä kohti ja palvelevat edelleen suurta yleisöä. Tämä tutkimus pyrkii selvittämään miten pienet ympäristövastuullisuuteen pohjautuvat yritykset voivat kilpailla tällaisten isojen yritysten joukossa pitäen kiinni periaatteistaan yhdessä kilpailluimmista aloista. Toinen näkökulma tutkimukselle on disruption esiin tuominen, sen tarkoituksen selventäminen ja selvittää ovatko suomalaiset mikrokokoiset tekstiilialan yritykset disruptiivisia tai onko niillä disruptiivista potentiaalia. Näkökulmaa lähestytään tutkimalla disruption alkuperäistä merkitystä Christensenin mukaisesti, mutta myös ottaen huomioon käsitteen arkikielistyminen. Tutkimus osoittaa pienen otoksen kautta, että ympäristökestävien yritysten motiivit kallistuvat vahvasti yhteiskunnallisiin motiiveihin sivuten yrittäjien ei-rahallisia motiiveja. Tämä viittaa siihen, että vastauksista käy ilmi aito huoli ympäristön tilasta ja valmiudet pyrkiä ratkaisemaan ongelmat, joita maailmaa huomattavasti saastuttava ala aiheuttaa. Ottaen huomioon disruptiivisuuden käsitteen alkuperäisen tiukan linjauksen sekä muuntuneen arkikielistyneen tarkoituksen, on vaikea sanoa ovatko tällaiset pienet yritykset todella disruptiivisia, mutta disruptiivista potentiaalia niissä on. Tutkimuksessa otetaan esiin uusia täydentäviä tutkimuskohteita sekä havaitaan, että disruptiivisuuden toteaminen ei välttämättä olekaan niin yksiselitteistä ennen kuin itse disruptio on tapahtunut.